Integrating Aquaponics to Enhance Ecological Awareness and Promote Sustainability-Oriented Competencies among Islamic High School Students in Labuhanbatu Selatan Regency - Rivo Hasper Dimenta; Rusdi Machrizal; Khairul Khairul; Amin Harahap (International Journal of Community Service Implementation, 2026)
Sustainable food security and environmental literacy require contextual and practice-based learning approaches in high school education. This community engagement program introduced a school-based aquaponic learning intervention designed to enhance students’ ecological reasoning and sustainability awareness. The activity was carried out in August 2025 at Islamic High School of MA Swasta Irsyadul Islamiah, Tanjung Medan District, Labuhanbatu Selatan Regency, involving 32 students. The intervention combined structured conceptual sessions, guided technical demonstrations, supervised system construction, and reflective evaluation. Learning outcomes were assessed using pre- and post-intervention instruments complemented by observational documentation. Quantitative analysis indicated a marked improvement in students’ academic performance, with average scores increasing from 58.4 (SD = 12.5) prior to the intervention to 82.7 (SD = 8.9) afterward. Statistical testing using a paired-samples t-test confirmed that this gain was significant (t(31) = 8.76, p < 0.001). Field observations further revealed strengthened collaborative participation and heightened interest in environmentally responsible practices. In addition to cognitive gains, the program produced a permanent instructional facility in the form of an operational aquaponic unit that supports continued experiential learning. The findings provide empirical support for integrating recirculating cultivation systems into biology instruction as a strategy for advancing ecological literacy and applied scientific skills. This initiative offers a transferable framework for schools seeking context-responsive, resource-efficient models to reinforce sustainability-oriented education